Knowledge on Post Exposure Prophylaxis of HIV among Nurses in a Hospital of Pokhara - Thapa, Manu; Gurung, Bishnu (Janapriya Journal of Interdisciplinary Studies, 2018)
Health care providers are at risk of acquiring human immunodeficiency virus (HIV) infection from occupational exposure, with nurses being the most vulnerable. Post exposure prophylaxis (PEP) of HIV is the only way to reduce risk of HIV after potential exposure. A study was conducted on Nurses Knowledge on PEP of HIV at Gandaki Medical College (GMC), Pokhara to find out the knowledge on PEP of HIV among nurses. Descriptive cross sectional research design was used for the study. Probability stratified systematic random sampling technique was used for sampling and self administered questionnaires was used for data collection with sample size of 90 nurses working in GMC. The data was analyzed using Statistical Package for Social Science (SPSS) version 20 software programme and presented in terms of frequency distribution, percentage, mean and standard deviation. For inferential statistics, chi square test was used at 5% level of significance. The findings of the study revealed that mean age of the respondents was 24.57 with standard deviation 3.43. Out of 90 respondents majority (83.3%) of the respondents were PCL passed and 47.8% of the respondents had adequate knowledge regarding PEP of HIV. The study found no significant association between demographic variables and knowledge level. It can be concluded that the nurses need to improve their level of knowledge on PEP of HIV by participating in different training programs. Health institution should also conduct continue nursing education programme to improve and update knowledge among the employees.